INOVASI KURIKULUM PENDIDIKAN ISLAM DI PERGURUAN TINGGI: INTEGRASI TAUHID, SAINS, DAN TEKNOLOGI - Iqbal Anggia Yusuf; Faiz Musthofa Abbas (Program Studi Pendidikan Agama Islam, 2025)
Curricular innovation in Islamic education represents a strategic effort to address the challenges posed by the advancement of science and technology while preserving the authenticity of tawhid values. Within the context of Islamic higher education, the integration of tawhid, science, and technology is essential for cultivating a generation with a strong spiritual foundation, mastery of modern knowledge, and adaptive technological skills. This study aims to analyze the forms of curricular innovation in Islamic higher education with a particular focus on the integration of these three dimensions. Employing a qualitative approach through a literature study, the research examines relevant scholarly works from journals, books, and academic policy documents. The findings indicate that curricular innovation can be realized through integrative instructional design, the reinforcement of interdisciplinary courses, and the implementation of project-based learning models that connect faith with the application of science and technology. Such integration not only strengthens students’ Islamic identity but also enhances their competitiveness in the era of globalization. Furthermore, an innovative and integrative curriculum has the potential to produce graduates who serve as agents of change, grounded in tawhid, equipped with scientific knowledge, and competent in the practical use of technology.